Efeito da Cloração da Água de Beber e do Nível Energético da Ração sobre o Ganho de Peso e Consumo de Água em Frangos de Corte - Furlan, Renato Luis [UNESP]; Macari, Marcos [UNESP]; Malheiros, Euclides Braga [UNESP]; Ingraci, Caetano [UNESP]; Meireles, Helena Torres [UNESP] (My University, 1999)
Two experiments were conducted to study the effect of adding chlorine on drinking water and different dietary energy levels on the body weight gain and water intake in broiler chickens. In Experiment 1, broilers were fed diets containing two levels of energy (2900 and 3200 kcal ME/kg) in each growing phase. The dietary energy level did not affect the water intake and the body weight gain of the broilers. In experiment 2, the dietary metabolizable energy level was 3200 kcal ME/kg and drinking water was treated with sodium hypochlorine at 11% corresponding to 5 ppm of chloride. The water intake was reduced in the birds that received chlorated drinking water, however, there was no reduction on body weight gain in birds that received sodium hypochlorine. The addition of chlorine to the drinking water improved the bacteriological index. The results obtained in this experiment evidence that the tested dietary energy level did not affect the broiler water intake; however, the addition of chlorine reduced the drinking water intake without influence on body weight gain of the treated birds.
Effect of Drinking Water Chlorination and Dietary Energy Level on Body Weight Gain and Water Intake in Broiler Chickens
Keywords: Broiler; Drinking water; Energy; Sex; Sodium hypochlorine